PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV DI SEKOLAH DASAR - Surya B Rajagukguk; Bramianto Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the use of a monotonous learning model where each lesson uses a conventional model (lecture) whice causes student to lack participation in science laearning which causes students to be less able to explore their potentitial in terms of their learning outcomes. The aim of this research is to determine Guided Inquiry model to improve student learning outcomes in the science and science subject material How to get all our needs in grade IV in elementary school. The type of research used is a Quasi-Experimental research method, nonequivalent control group design. The population in this study was 45 students, with class IV-A consisting of 22 students as the experimental class and IV-B consisting of 23 students as the control calss. The data collection instrument in this research used a test instrument in the form of a pretest-posttest with 15 multiple choice questions. The data obtained were analyzed using the normality test, homogenetic test, hypothesis test (independent t-test). The results of the t-test calculation with 5% level requirement obtained a ttabel of 2.03 and a tcount of 6,95. Based on the hypothesis testing criteria, tcount > ttable is obtained, namely 6.95 > 2.03. Therefore, it can be coucluded that H0 is accepted. Based on this, it can be stated that there is a significant influence of using the Guided Inquiry learning model in improving student learning outcomes in science and science subjects in class IV elementary school.